2020
DOI: 10.1177/1540415320923568
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Psychosocial Factors, Substance Use Behaviors, and Sexual Behaviors by Self-Reported HIV Status Among Middle-Aged Hispanic Men Who Have Sex With Men

Abstract: Introduction: Human immunodeficiency virus (HIV) is a significant health issue among Hispanic men who have sex with men (MSM). Despite existing research, no studies have compared psychosocial factors by self-reported HIV antibody status. Method: Participants ( n = 150) completed measures of social support, loneliness, depressive symptoms, substance use, and sexual behaviors. Results: Participants with a self-reported HIV-antibody positive status reported lower levels of social support and higher levels of illi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Many studies have investigated problematic alcohol and recreational drug use trajectories in PLHIV, particularly in the contexts of stress, coping, and sexual risk-taking ( Glynn et al, 2019 , Mimiaga et al, 2013 , Moitra et al, 2020 , Pence et al, 2008 , Rosen et al, 2017 , Wardell et al, 2018 ). Prior studies have found that problematic alcohol consumption and recreational drug use commonly co-occur with other adverse psychosocial conditions, including depressive symptoms, loneliness, and inadequate social support ( Javanbakht et al, 2020 , Mannes et al, 2016 , Rubtsova et al, 2017 , Siconolfi et al, 2013 , Valdes et al, 2021 ). Problematic alcohol, heavy marijuana, and recreational drug use are linked to suboptimal HIV outcomes and quality of life, including sexual risk-taking, impaired cognitive function, non-adherence to HIV care recommendations, weakened immunity, and premature mortality ( American Addiction Centers, 2021 , Bensley et al, 2018 , Brown et al, 2019 , Duko et al, 2019 , Millar et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated problematic alcohol and recreational drug use trajectories in PLHIV, particularly in the contexts of stress, coping, and sexual risk-taking ( Glynn et al, 2019 , Mimiaga et al, 2013 , Moitra et al, 2020 , Pence et al, 2008 , Rosen et al, 2017 , Wardell et al, 2018 ). Prior studies have found that problematic alcohol consumption and recreational drug use commonly co-occur with other adverse psychosocial conditions, including depressive symptoms, loneliness, and inadequate social support ( Javanbakht et al, 2020 , Mannes et al, 2016 , Rubtsova et al, 2017 , Siconolfi et al, 2013 , Valdes et al, 2021 ). Problematic alcohol, heavy marijuana, and recreational drug use are linked to suboptimal HIV outcomes and quality of life, including sexual risk-taking, impaired cognitive function, non-adherence to HIV care recommendations, weakened immunity, and premature mortality ( American Addiction Centers, 2021 , Bensley et al, 2018 , Brown et al, 2019 , Duko et al, 2019 , Millar et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%